Assessing the Preparedness for Emergency Management of Status Asthmaticus in Pediatric Patients’ among EMS Professionals, Pune, India - Parag Rishipathak; Navnita Sengupta; Anand Hinduja; Neha Ahire (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Asthma is one of the most common diseases affecting children. Children affected by Asthma need recurrent hospitalization and show high degree of absenteeism in schools due to exacerbations. It is characterized as a state of hyper responsiveness triggered by allergens such as pollens, foods, dust mites and animal dander which irritate and cause bronchoconstriction. EMS professionals shoulder great responsibility in pediatric respiratory emergencies as their actions determine the long term quality of life of these childrenAim: The present study is aimed at assessing the preparedness with regards to management of Status Asthmaticus amongst EMS professionals in Pune, India.Methodology: The study was conducted amongst 189 Emergency medical Services professionals residing in Pune India. A pretested and validated questionnaire was utilized for the study. The questionnaire consisted of 21 items meant to assess the knowledge and skills with regards to Emergency Management of Status Asthmaticus amongst EMS professionals. Each correct answer was given a score of one with maximum score of 21. The questionnaire was administered online.Result: EMS professionals showed average level of preparedness with reference to management of Status Asthmaticus. Conclusion: EMS professionals need periodic training to improve their level of knowledge and skills. Simulation play a pivotal role in augmenting the skills of EMS professionals in order to identify suspected cases and provide accurate emergency management.